Analysis of Burger Main Raw Material Inventory Control Using the Economic Order Quantity (EOQ) Method and the Just in Time (JIT) Method - Rahmadini, Reny; Nurainun, Tengku; Hartati, Misra; Lubis, Fitriani Surayya; Nur, Muhammad (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2026)
Burger Fandawa is an MSME in Pekanbaru that faces problems in managing the inventory of the main raw materials, namely bread, meat, and sauce. The main problem is the uncertainty of demand and inventory irregularities that cause shortages or excess stock, thus disrupting smooth production and cost efficiency. This study aims to analyze the main raw material inventory management method using the Economic Order Quantity (EOQ) and Just In Time (JIT) approaches to determine the most optimal method. The research method used is quantitative analysis based on demand data, ordering costs, storage costs, and lead time of the main raw materials during 2023. The results of the analysis show that the optimal purchase quantity according to EOQ is 236.505 packs of bread, 93.510 kg of meat, and 118.866 kg of sauce, with a total inventory cost of IDR. 2,763,809,416. Meanwhile, the JIT method results in a lower total inventory cost of IDR. 1,142,030,936, with a savings difference of IDR. 1,621,778.48. Based on these results, the JIT method is considered more optimal for managing raw material inventory at Burger Fandawa. The JIT method is more efficient in reducing inventory costs and increasing the effectiveness of managing the main raw material stocks.